L’araldica immaginaria e il Libro della Natione Normanda (Universidad de Sevilla, Biblioteca, A 332/142) - Savorelli, Alessandro (Eikón / Imago, 2025)
The ms. entitled Book of the Norman Nation, preserved in the University Library of Seville (by an unknown author of the 17th century) contains coats of arms, portraits of sovereigns and family trees of the dynasties reigning in Naples from the Normans to the Habsburgs. Some tables placed at the end of the work illustrate ficititious coats of arms assigned to various ancient characters and peoples, copied from foreign sources, and a table with flags full of heraldic signs attributed to dominions from the Greeks, to the Goths, to the Lombards, up to the Franks and the Saracens. It is an example of imaginary heraldry, built on anachronisms, but partly original compared to other testimonies of the time, as figures of a fantastic nature are renounced in favor of heraldic compositions freely inspired by those of the capital cities of Campania.